2008
DOI: 10.1007/s00280-008-0711-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of cisplatin nephrotoxicity: state of the art and recommendations from the European Society of Clinical Pharmacy Special Interest Group on Cancer Care

Abstract: Antineoplastic drugs used in the treatment of cancers present with variable renal tolerance profiles. Among drugs with a potential for renal toxicity, platinum salts, and especially cisplatin is a well-known agent that may induce acute and chronic renal failure. The mechanisms of its renal toxicity and the means of its prevention are presented in this article which represent the Clinical Recommendation from the Special Interest Group on Cancer Care of the European Society of Clinical Pharmacy (ESCP).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
166
1
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(178 citation statements)
references
References 41 publications
7
166
1
4
Order By: Relevance
“…However, cisplatin also induces undesired side effects in normal tissues or organs, especially in the kidney (3)(4)(5)(6)(7)(8). Nephrotoxicity or acute kidney injury (AKI) 4 occurs in over one quarter of the patients receiving cisplatin treatment and AKI has been reported to be related to the increased mortality in the long-term survivors of these patients (3)(4)(5)(6)(7). Years of research has led to the identification of the main signaling pathways that are activated by cisplatin in kidneys and contribute to AKI, such as mitogen-activated protein kinase (MAPK), P53 and related DNA damage response, NF-B, and other signaling pathways.…”
mentioning
confidence: 99%
“…However, cisplatin also induces undesired side effects in normal tissues or organs, especially in the kidney (3)(4)(5)(6)(7)(8). Nephrotoxicity or acute kidney injury (AKI) 4 occurs in over one quarter of the patients receiving cisplatin treatment and AKI has been reported to be related to the increased mortality in the long-term survivors of these patients (3)(4)(5)(6)(7). Years of research has led to the identification of the main signaling pathways that are activated by cisplatin in kidneys and contribute to AKI, such as mitogen-activated protein kinase (MAPK), P53 and related DNA damage response, NF-B, and other signaling pathways.…”
mentioning
confidence: 99%
“…In addition, several investigators have reported that persistent hypomagnesemia might be associated with renal damage after chemotherapy. 30,31 Therefore, management of longterm hypomagnesemia is one candidate, although it is not clear at present whether correction of hypomagnesemia improves renal function.…”
Section: Discussionmentioning
confidence: 99%
“…Oxaliplatin, unlike cisplatin, has been reported to have minimal effect on kidneys in humans and rats. 18,19 In their study of the pharmacokinetic and toxicodynamic relationships of platinum compounds, Hanada et al reported that the reason for the differential in vivo susceptibility of oxaliplatin and cisplatin to nephrotoxicity (at the doses used in their work) is pharmacokinetic in origin and the oxaliplatin total clearance was the highest among other platinum compounds. 20 In this work we have shown that both cisplatin and oxaliplatin are equi-effective in inducing a state of oxidative stress in HEK cells.…”
Section: Discussionmentioning
confidence: 99%